A new species of sucking louse (Psocodea: Phthiraptera: Anoplura: Hoplopleuridae) from the pale field rat, Rattus tunneyi (Rodentia: Muridae), in Australia - Wang, Wei; Durden, Lance A.; Shao, Renfu (Zootaxa, 2022)
We describe and illustrate a new species of sucking louse, Hoplopleura tunneya new species, from the Australian pale field rat, Rattus tunneyi Thomas (Rodentia: Muridae). Currently, 22 species of the genus Hoplopleura Enderlein, 1904 (Phthiraptera: Anoplura: Hoplopleuridae) are known from Australian endemic rodents. Among the seven “new endemic” rodent species of the genus Rattus in Australia, R. tunneyi is one of five hosts to Hoplopleura lice. In addition, we give a list of all the species of Hoplopleura known from Australian endemic rodents. Including the introduced species Polyplax spinulosa, the total number of sucking louse species known from Australian endemic rodents is now 24.